Examination and current state of vegetation of technologically disturbed lands of SSGPO (Eurasian Journal of Ecology, 2019)
For the biological stage of reclamation of disturbed lands, the study of plant communities, theidentification of dominant species and potential phytomeliorants of the local flora that are resistant to acomplex of unique environmental conditions of technogenic formations are of paramount importance.The study of the comparative characteristics of natural and artificial vegetation overgrown with manmade man-made vegetation in the relationship of exploration of the subsoil by the open method, regimeof disturbed land allotment, landscape, soil conditions and vegetation cover is a very important task.The purpose of our research is to study the processes of natural overgrowing of dumps, the analysisof the results of previously carried out works on reclamation.The study of the composition and structure of vegetation industrial dumps and adjacent areas wascarried out using traditional methods of field geobotanical research.We have analyzed the previous studies on the composition and structure of the vegetation of theSokolov-Sarbay mining and processing production association (SSGPO), according to literary sources,local flora has been identified. By means of own research, an assessment of the current state of vegetation has been carried out, potential phytomeliorants have been identified for the subsequent biologicalstage of reclamation of disturbed lands located in similar natural and climatic zones of the republic.The vegetation of a flat plateau-shaped dump mainly consists of formed by self-overgrown communities. Communities of steppe cereals and motley grass dominate. On the periphery of the dump,meadow cereals and motley grasses dominate along dug trenches. It consists mainly of herbaceous perennials, but the role of annuals and one--two-year-olds is also quite large. The phytocenoses are dominated by steppe species, from the ecological groups of plants – xerophytes. The participation of weedplants is small. At the end of 60 years after the formation of the dump, we can conclude that the naturalzonal vegetation is almost restored – zonal steppe grass and forbs dominate in the vegetation cover, withthe exception of artificially formed negative relief elements, where mosaic patterns are observed due tochanges in the environmental conditions of the habitat.Key words: vegetation, phytomeliorants, dominants, disturbed lands, dumps.